Penerapan model pembelajaran berbasis proyek (PjBL) project based Learning dalam meningkatkan kreativitas siswa melalui market day - Muhammad Adi Saputra; Liany Fitriadi; Putri Windi Melinda; Yayan Sudrajat (SINAU : Jurnal Ilmiah Pendidikan dan Pembelajaran, 2023)
This study discusses the application of the Project Based Learning Learning Model to increase student learning creativity. The purpose of this research is to find out how to increase student creativity with the Project Based Learning model. This research is a qualitative research using descriptive method, which describes and reveals the process and results of student learning creativity. The object of research is creativity, learning models and market day. The work product serves as material for testing and assessing the competence of students. The results of this study indicate an increase in student creativity.